Cytotoxic Effects of Thiamethoxam in the Midgut and Malpighian Tubules of Africanized Apis mellifera (Hymenoptera: Apidae) - Catae, Aline Fernanda [UNESP]; Roat, Thaisa Cristina [UNESP]; De Oliveira, Regiane Alves [UNESP]; Ferreira Nocelli, Roberta Cornelio; Malaspina, Osmar [UNESP] (Wiley-Blackwell, 2014)
Due to its expansion, agriculture has become increasingly dependent on the use of pesticides. However, the indiscriminate use of insecticides has had additional effects on the environment. These products have a broad spectrum of action, and therefore the insecticide affects not only the pests but also non-target insects such as bees, which are important pollinators of agricultural crops and natural environments. Among the most used pesticides, the neonicotinoids are particularly harmful. One of the neonicotinoids of specific concern is thiamethoxam, which is used on a wide variety of crops and is toxic to bees. Thus, this study aimed to analyze the effects of this insecticide in the midgut and Malpighian tubule cells of Africanized Apis mellifera. Newly emerged workers were exposed until 8 days to a diet containing a sublethal dose of thiamethoxam equal to 1/10 of LC50 (0.0428 ng a.i./l L of diet). The bees were dissected and the organs were processed for transmission electron microscopy. The results showed that thiamethoxam is cytotoxic to midgut and Malpighian tubules. In the midgut, the damage was more evident in bees exposed to the insecticide on the first day. On the eighth day, the cells were ultrastructurally intact suggesting a recovery of this organ. The Malpighian tubules showed pronounced alterations on the eighth day of exposure of bees to the insecticide. This study demonstrates that the continuous exposure to a sublethal dose of thiamethoxam can impair organs that are used during the metabolism of the insecticide. Microsc. Res. Tech. 77:274-281, 2014. (c) 2014 Wiley Periodicals, Inc.
Keywords: honeybees; neonicotinoid; metabolism; insecticide toxicology